ANALYSIS OF PREVENTING GROWTH FALTERING THROUGH IMPROVING CHILD NUTRITION BY CONSUMING SUPPLEMENTARY FOODS PROCESSED FROM SEAFOOD IN NELAYAN INDAH VILLAGE - Fakhri Widyanto; Hendriawan, Hendriawan; Ragil Wahyuda Abrar (Ikatan Dosen Menulis, 2025)
Nutritional needs of children are the amount and type of nutrients needed to support the physical and mental growth and development of children aged 1-5 years. These needs include carbohydrates, proteins, fats, vitamins, and minerals, all of which contribute to optimal health, a strong immune system, and cognitive development. One form of complementary food is food derived from seafood sales leftovers, which can still be reprocessed into nutritious foods. The purpose of this study was to examine the relationship between providing additional food from processed seafood as an improvement in nutritional intake and preventing growth retardation in children in the Nelayan Indah Village, Medan City. The research method used a quantitative correlational approach with a cross-sectional approach. The study sample was 76 mothers with children aged 1-5 years in the Nelayan Indah Village, Medan City. The research data were analyzed using univariate and bivariate tests with p-values to see the relationship between the studied variables, using SPSS version 24 for Windows. The study found that consuming seafood supplements had a 54.7% effect, improving nutritional intake had a 50.6% effect, and socioeconomic conditions had a 53.4% effect on the incidence of growth faltering in children aged 1-3 years. The study recommended that village governments conduct outreach and training on making healthy seafood-based foods.